An analysis of price and volatility transmission in butter, palm oil and crude oil markets - Dennis Bergmann; Declan O'Connor; Andreas Thümmel (Agricultural and Food Economics, 2016)
Recent changes to the common agricultural policy (CAP) saw a shift to greater market orientation for the EU dairy industry. Given this reorientation, the volatility of EU dairy commodity prices has sharply increased, creating the need to develop proper risk management tools to protect farmers' income and to ensure stable prices for processors and consumers. In addition, there is a perceived threat that these commodities may be replaced by cheaper substitutes, such as palm oil, as dairy commodity prices become more volatile. Global production of palm oil almost doubled over the last decade while butter production remained relatively flat. Palm oil also serves as a feedstock for biodiesel production, thus establishing a new link between agricultural commodities and crude oil. Price and volatility transmission effects between EU and World butter prices, as well as between butter, palm oil and crude oil prices, before and after the Luxembourg agreement, are analysed. Vector autoregression (VAR) models are applied to capture price transmission effects between these markets. These are combined with a multivariate GARCH model to account for potential volatility transmission. Results indicate strong price and volatility transmission effects between EU and World butter prices. EU butter shocks further spillover to palm oil volatility. In addition, there is evidence that oil prices spillover to World butter prices and World butter volatility.
Keywords: 330; Volatility transmission; Price transmission; Dairy industry; Palm oil; Multivariate GARCH; VAR